2017
DOI: 10.1039/c7cp04413e
|View full text |Cite
|
Sign up to set email alerts
|

Periodic DFT+U investigation of the bulk and surface properties of marcasite (FeS2)

Abstract: Marcasite FeS2 and its surfaces properties have been investigated by Hubbard-corrected DensityFunctional Theory (DFT+U) calculations. The calculated structural parameters, interatomic bond distances, elastic constants and electronic properties of the bulk mineral were determined and compared with earlier theoretical reports and experimental data where available. We have also investigated the relative stability, interlayer spacing relaxations, work function, and electronic structures of the {010}, {101}, {110} … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 105 publications
5
24
0
Order By: Relevance
“…The orthorhombic system has 9 independent values for elastic constants and 3 for dielectric constants which reflects anisotropic properties. Elastic properties from classical simulations are in very good agreement with DFT/PBE+U calculations 12,15 and experiment (bulk modulus B of 146. The mineral is then easiest to distort upon a shear stress rather than compression.…”
Section: Bulksupporting
confidence: 72%
See 2 more Smart Citations
“…The orthorhombic system has 9 independent values for elastic constants and 3 for dielectric constants which reflects anisotropic properties. Elastic properties from classical simulations are in very good agreement with DFT/PBE+U calculations 12,15 and experiment (bulk modulus B of 146. The mineral is then easiest to distort upon a shear stress rather than compression.…”
Section: Bulksupporting
confidence: 72%
“…Few theoretical studies have reported surface energies of marcasite. The main results from DFT studies 15,35 are in Table 3 for comparative purpose. The order of surface energies after relaxation, calculated with force field, is as follows: < (010) < (001) < (111) < (121) < (102) < (103) < (031) < (305) < (100) < (130) < (211) < (011) < (201) < (120) < (021) < (210) < (110)…”
Section: Calculated Surfaces and Morphologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dipole correction perpendicular to all surfaces was accounted for, which ensured that there is no net dipole perpendicular to the surfaces that may affect the potential in the vacuum level. [51][52][53] 3. Results and discussions…”
Section: Methodsmentioning
confidence: 99%
“…The elastic properties of materials give the data necessary in understanding the bonding property between adjacent atomic planes, stiffness, bonding anisotropic and structural stability of the material [35,36]. Shown in Table 2 are the calculated single crystal elastic constants of the αand β-SrZrS 3 materials, all of which satisfy the Born's mechanical stability criteria for orthorhombic structures [37], indicating that both materials are mechanically stable under ambient conditions.…”
Section: Mechanical Propertiesmentioning
confidence: 99%